Sustainable Energy Systems: Efficiency and Optimization (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book explores how the concepts, methods and tools of systemic analyses have been utilised in various contexts, and at different levels, to improve the efficiency and optimisation of sustainable energy systems.